A comprehensive review of international research using the Behavioral and Emotional Rating Scale. Issue 3 (3rd July 2019) - Lambert, Matthew C.; Sointu, Erkko T.; Epstein, Michael H.
ABSTRACT: Child assessment practices have undergone, and are continuing to undergo, significant changes. Among the most prominent changes is the movement toward measuring child well-being, in general, and emotional and behavioral strengths, in particular. The Behavioral and Emotional Rating Scale (BERS) is a strength-based instrument which is widely used in the United States and is beginning to be used internationally. The purpose of this review was to assess the translation adaptation process and to determine the psychometric properties of the BERS scores when used in countries other than the United States. Results from 15 international studies indicated that the researchers followed acceptable standards for test adaptation and the BERS scores generally met acceptable professional standards for reliability and validity. The limitations with the review process and the published studies were identified, as well as the directions for future research and implications for professional practice.